RETROSPECTIVE EVALUATION OF PATIENTS WITH LANGERHANS CELL HISTIOCYTOSIS FOLLOWED IN OUR CLINIC - Mehmet Can Ugur (Elsevier, 2021)
Objective: Langerhans cell histiocytosis (LCH) is a rare histiocytic disorder that can be especially seen in children and young adults. The clinical presentation of patients with LCH varies according to the sites of involvement. In about half of patients, the disease is limited to a single organ system and bone involvement is very common. In this study, it was aimed to retrospectively evaluation the patients diagnosed with LCH who were followed up and treated in our clinic. Methodology: The data of patients over the age of 18 years who were followed up and treated in Bozyaka Training and Research Hospital Hematology Clinic between 2015-2021 were scanned retrospectively from the hospital system. Results: Data of 6 patients were obtained. The mean age of the patients was 33.6. There was no difference between the genders. Pain was the reason for admission in 4 patients and was the most common symptom. While the most frequently involved system was the skeletal system with 5 patients, lung involvement was seen in 2 patients. Vinblastine and prednisolone combination therapy was given to 1 patient, who developed steroid-related avascular necrosis. One patient who was planned for combination treatment Conclusion: LCH is a rare disease especially seen in children and young adults. It can involve the skeletal system, lungs, and other organs. The prognosis is often good with excision of the lesion or systemic treatment.